A longitudinal study evaluating interim assessment of neoadjuvant chemotherapy for bladder cancer. (19th September 2021) - Furrer, Marc A.; Papa, Nathan; Luetolf, Sandro; Roth, Beat; Cumberbatch, Marcus; Dorin Vartolomei, Mihai; Thomas, Benjamin C.; Thoeny, Harriet C.; Seiler, Roland; Thalmann, George N.; Kiss, Bernhard
Abstract : Objectives: To evaluate the usefulness of radiological re‐staging after two and four cycles of neoadjuvant chemotherapy (NAC), the impact of re‐staging on further patient management, and the correlation between clinical and final pathological tumour stage at radical cystectomy (RC). Patients and Methods: We conducted a longitudinal, single‐centre, cohort study of prospectively collected consecutive patients who underwent NAC and RC for urothelial muscle‐invasive bladder cancer between July 2001 and December 2017. Patients underwent repeated computed tomography scans for re‐staging after two cycles of NAC and after completion of NAC before RC. Results: Of 180 patients, 110 had ≥four cycles of NAC and had complete imaging available. In the entire cohort, further patient management was only changed in 2/180 patients (1.1%) after two cycles of NAC based on radiological findings. Patients who were stable after two cycles but then downstaged after at least four cycles of NAC had a similarly lowered risk of death (hazard ratio [HR] 0.53). Only one patient downstaged after two cycles was subsequently upstaged after four cycles. Clinical downstaging was observed in 51 patients (46%), 55 patients (50%) had no change in clinical stage and four patients (3.6%) were clinically upstaged. Patients clinically downstaged after four cycles of NAC had a lower risk of death (HR 0.49, 95% confidence interval 0.25–0.94; P  = 0.033) compared to those with no change or upstaged after completion of NAC. Conclusions: Re‐staging of muscle‐invasive bladder cancer after two cycles of NAC offers little additional information, rarely changes patient management, and may therefore be omitted, whereas re‐staging after completion of NAC by CT is a strong predictor of overall survival.